TINJAUAN KESIAPAN KERJA OPERATOR A2B DAN DUMP TRUCK TERHADAP MOBILISASI UNIT DI PT.PAMA PERSADA NUSANTARA DISTRICT KPC SANGATTA - Praja, Septian Adi (PREDIKSI, 2016)
he purpose of this study was to find out A2B Operator Job Readiness and Mobilization Against Unit Dump Truck In PT.Pama Persada Nusantara Sangatta District KPCS. The timing of the research conducted in January 2016 through May 2016 for five (5) months.The research method in this study is a qualitative descriptive research on how the Work Readiness A2B And Dump Truck Operator Mobilization Against Unit. The collection of data by distributing questionnaires, observation and interviews.The study states that the Work Readiness A2B And Dump Truck Operator Mobilization Against Unit In PT.Pama Persada Nusantara District KPCS Sengata run well by filling the form fit to work, which is expected to be filled with honest work to prevent accidents on employees of PT. Pama Persada Nusantara part opreator A2B and Dump Truck on job sites and is always ready to work.